The Growth of Tagetes patula Linn. and Its Ability to Reduce Cr(VI) with the Addition of Microbacterium sp. SpR3 - Novellasari, Firdiana; Meitiniarti, V. Irene; Seleiman, Mahmoud F.; Kasmiyati, Sri (Biosaintifika: Journal of Biology & Biology Education, 2023)
Cr(VI) is a heavy metal that has the potential to become a soil pollutant and has an impact on organisms. The contamination caused by Cr(VI) could be alternatively treated with bioremediation techniques. The current study aimed to determine the most potential combination of Tagetes patula Linn. and Microbacterium sp. strain SpR3 for remediation of soil Cr(VI) contamination based on growth of T. patula. The application of SpR3 applied at the 1st day (T0) and 20th day (T20) with 10 g (M10), 30 g (M30), 50 g (M50) of bacterial inoculum to T. patula grown under Cr(VI; 100 mg/L). The results showed that T0M50 treatment resulted in the highest values of growth traits of T. patula grown under Cr(VI) metal stress. The highest BC value (0.36) was obtained from plants treated with T2M10 and T2M50, while the highest TF value (0.08) obtained from plants treated with T0M50. BC value 1 means that the combination of T. patula and SpR3 bacteria for heavy metal Cr(VI) can be classified as an excluder and the TF value 1 means that the combination can act as a phytostabilization in handling Cr(VI) contamination. In conclusion, the application of SpR3 using T0M50 can enhance the growth of Tagetes patula Linn. grown under Cr(VI) stress condition. The outcome of the study are expected to advancement in the application of rhizobacterial and plant combined system in the bioremediation of soil Cr(VI) contaminated.